Clinical outcomes of endovascular therapy with vascular stents for central venous obstruction in hemodialysis patients. Issue 5 (November 2022) - Nakao, Masashi; Inagaki, Yusuke; Hata, Takehiro; Morioka, Yuta; Otsuki, Hisao; Arashi, Hiroyuki; Yamaguchi, Junichi; Hagiwara, Nobuhisa
Abstract: Background: Symptomatic central venous obstruction (CVO) is sometimes observed in patients undergoing hemodialysis. Angioplasty is generally performed for salvage purposes, and stent implantation is performed as a last resort to prevent permanent venous occlusion. However, published reports about the clinical outcomes of stenting for CVO have been limited by the small number of included patients and the relatively old generation of analyzed stents. This study aimed to clarify the safety and efficacy of endovascular therapy (EVT) using stents for symptomatic CVO in contemporary practice. Methods: This retrospective review was performed between May 2012 and August 2021. We retrospectively analyzed consecutive 31 lesions (31 patients, 64 ± 10.7 years old) treated with a vascular stent for elastic recoil after balloon angioplasty or recurrent stenosis <3 months after angioplasty. The primary outcome was primary patency, defined as freedom from target lesion revascularization. The secondary outcome was assisted primary patency, defined as freedom from permanent occlusion of the target stents. Results: In all cases, stents were successfully deployed on the target lesions. No EVT-related complications were observed. Self-expandable and balloon-expandable stents were used in 26 and 5 lesions, respectively. The median follow-up period was 18 months (interquartile range, 7–40). Kaplan-Meier analysis revealed that the primary patency rates were 66.1 % at 6 months, 61.7 % at 12 months, and 38.4 % at 24 months after EVT. The assisted primary patency rate was 70.3 % 24 months after EVT. In the multivariate analysis, younger age was the only independent predictor of target lesion revascularization (hazard ratio: 0.92, 95 % CI: 0.85–0.99, p = 0.04). Conclusions: Stent implantation for CVO that is resistant to standard angioplasty seems safe and effective. Graphical abstract: Unlabelled Image Highlights: Endovascular therapy with stents for central venous obstruction in patients receiving hemodialysis is safe. Midterm patency rates seem acceptable in contemporary practice. Young age is a predictor of clinically driven, target lesion revascularization.